Pengaruh Kemampuan Awal dan Minat Belajar Terhadap Prestasi Belajar Bahasa Arab Siswa Kelas XI MIPA SMA Majlis Tafsir Al-Qur’an Tahun Ajaran 2022/2023 - Anggi Sapitha (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2022)
The type of research used by the researcher in this study is quantitative research. The approach employed is an inferential approach to analyze the relationships between variables by testing hypotheses. The method used is the survey method, which is applied to explain causal relationships and test hypotheses. The data sources obtained by the researcher are through observation, interviews, questionnaires (research surveys), and documentation. The data analysis technique in this study uses simple regression analysis and multiple linear regression analysis. Data analysis in this research is assisted by SPSS for Windows version 20.0. The research results show that: 1) There is an effect of initial ability on the Arabic language learning achievement of 11th-grade science students at SMA MTA Surakarta. This can be seen from the Sig. value of 0.000 < 0.05, with a coefficient value of 0.363 and t-count 5.882 > t-table 1.999, and an F-count of 34.588.2) There is an effect of learning interest on the Arabic language learning achievement of 11th-grade science students at SMA MTA Surakarta. This can be seen from the coefficient of determination (R Square) value of 0.084. 3) There is a simultaneous effect of initial ability and learning interest on the learning achievement of 11th-grade science students at SMA MTA Surakarta. This can be seen from the F-count value of 17.024 with a Sig. value of 0.000 < 0.05 and an R Square value of 0.362 (36.2%). The meaning of this figure is that initial ability and learning interest affect student achievement by 36.2%, while the remaining 63.8% is influenced by other variables.